2016
DOI: 10.1016/j.tox.2016.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of trimethoprim/sulfamethoxazole in a macaque model of HIV infection

Abstract: Background Sulfonamide hypersensitivity has a high incidence in HIV infection and correlates with low CD4+ counts, but the mechanisms are not understood. The aims of this study were to determine whether trimethoprim/sulfamethoxazole (TMP/SMX) led to SMX adduct formation, immunogenicity, or signs of drug hypersensitivity in SIV-infected rhesus macaques, and whether differences in antioxidants, pro-inflammatory mediators, or SMX disposition were predictive of drug immunogenicity. Methods Nine macaques chronica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 64 publications
2
1
1
Order By: Relevance
“…(Wong et al. ) Based on normal hepatic SMX‐HA reduction activities found in the present study, decreased urinary SMX‐HA in retroviral infection may reflect further oxidation of SMX‐HA to SMX‐NO (which is not detected in urine due to instability) rather than altered SMX‐HA reduction by cytochrome b 5 reductase.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…(Wong et al. ) Based on normal hepatic SMX‐HA reduction activities found in the present study, decreased urinary SMX‐HA in retroviral infection may reflect further oxidation of SMX‐HA to SMX‐NO (which is not detected in urine due to instability) rather than altered SMX‐HA reduction by cytochrome b 5 reductase.…”
Section: Discussionsupporting
confidence: 52%
“…We expanded on the relatively small group of animals available for hepatic expression arrays with activity assays in additional liver samples, and also found no difference in N-acetylation of SMX. Further, in a recent TMP/SMX dosing study in the same population of macaques, (Wong et al 2016) we found no differences in 24-hour urinary concentrations of N-acetylated SMX in SIV-infected versus control animals (54.4% of total urinary metabolites versus 55.1%, respectively, n = 7 in each group, P = 0.45). In HIV-infected patients, some studies have found impaired N-acetylation, using caffeine or dapsone as in vivo probe drugs, in individuals with normal NAT2 genotypes.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…In animal and in human studies, false positive SMX antibodies have been reported in individuals receiving TMP-SMX without any apparently clinical reaction, therefore this test would not be suitable for screening. 54 , 55 …”
Section: Investigation Of Patients With a History Of Tmp-smx Allergymentioning
confidence: 99%